2015
DOI: 10.2903/j.efsa.2015.4087
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the re‐evaluation of ascorbic acid (E 300), sodium ascorbate (E 301) and calcium ascorbate (E 302) as food additives

Abstract: The EFSA Panel on Food additives and Nutrient Sources added to Food (ANS Panel) provides a scientific opinion re‐evaluating the safety of ascorbic acid (E 300), sodium ascorbate (E 301) and calcium ascorbate (E 302) as food additives. The use of ascorbic acid and its salts as food additives was evaluated by the Joint FAO/WHO Expert Committee on Food Additives and by the Scientific Committee on Food. Ascorbic acid is absorbed from the intestine by a sodium‐dependent active transport process and, at low doses, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 108 publications
0
11
0
1
Order By: Relevance
“…In the same work, they showed higher antioxidant activity of a comfrey root extract compared to standard antioxidants through different methods, thus, evidencing that phenolic compounds seem to display a crucial role in comfrey root extract antioxidant effects [41]. Similarly, Neagu et al described the higher antioxidant activity of comfrey extracts processed by ultrafiltration than ascorbic acid [39], a common additive already used as a food preservative (E-300) [98].…”
Section: Biological Activity Of Comfreymentioning
confidence: 99%
See 1 more Smart Citation
“…In the same work, they showed higher antioxidant activity of a comfrey root extract compared to standard antioxidants through different methods, thus, evidencing that phenolic compounds seem to display a crucial role in comfrey root extract antioxidant effects [41]. Similarly, Neagu et al described the higher antioxidant activity of comfrey extracts processed by ultrafiltration than ascorbic acid [39], a common additive already used as a food preservative (E-300) [98].…”
Section: Biological Activity Of Comfreymentioning
confidence: 99%
“…Nowadays, conventional preservatives are synthetic chemical substances, which include some that are being re-evaluated, e.g., nitrates and nitrites by the corresponding authority due to their potential health risk [98]. In fact, over 60% of the population recognized to worry about the presence of food additives, including food preservatives in foods in 2010 [99].…”
Section: Biological Activity Of Comfreymentioning
confidence: 99%
“…Otros aditivos que se destacan y que son potentes antioxidantes son el ascorbato de sodio SIN301 y el ácido ascórbico SIN300 también conocido como vitamina C, ambos aditivos ampliamente usados en la industria alimentaria. Sobre el ácido ascórbico (SIN300) y su sal (SIN301), la Autoridad Europea de Seguridad Alimentaria determinó que no existía riesgo de su consumo diario (EFSA, 2015).…”
Section: Figura 1 Los 20 Aditivos Más Frecuentes En Alimentos Procesados Para Bebé Cochabambaunclassified
“…No information on reaction products of ascorbyl palmitate and stearate in food has been identified, but as the esters are in the 6-position of ascorbic acid, leaving the enediol structure of ascorbic acid free, it may be assumed that ascorbyl palmitate will react with other compounds similarly to ascorbic acid (Saltmarsh, 2013). Information on the reaction and fate in food of ascorbic acid has been revised by the Panel (EFSA ANS Panel, 2015).…”
Section: Reaction and Fate In Foodmentioning
confidence: 99%
“…Ascorbic acid and its salts (E 300-302) have been re-evaluated by the Panel (EFSA ANS Panel, 2015). It was concluded that the available data for ascorbic acid and its salts did not report any adverse effects in animal studies, even at the highest doses tested.…”
Section: Information On Existing Authorisations and Evaluationsmentioning
confidence: 99%